Growth and gonadal development of kerai lampam cultured in control environment - Mohamed, Norhasmariza (2016)
Kerai Lampan is a hybrid between Kerai Hypsibarbus wetmorei (Smith, 1931) male and Lampam Jawa Barbonymus gonionotus (Bleeker, 1846) female. Market price for Kerai Lampam is quite high at MYR25/kg. Even as a popular cultured food fish, there is no documented report on the growth, survival and gonadal development of Kerai Lampam. Therefore, the objectives of this study were to observe the growth, survival and gonadal development of Kerai Lampam cultured from 2 to 9 month-old. A total of 300 fry with weight 0.10±0.08g and length 1.87±0.32cm produced at the Institute of Bioscience hatchery, UPM, Serdang, Selangor, were cultured for 9 months period. The growth of these fingerlings was measured monthly based on their length and weight. Survival was noted throughout the study period. Gonads from ten fish were sampled randomly on monthly basis for histological observation starting from 4 month-old. At the same time fishes were also observed for their morphological differentiation. Fish achieved weight of 6.73±0.52g and length of 9.86±0.27cm at 9 month-old. However, no morphological differences observed to differentiate male and female fish at this stage. As for gonadal development, no mature ovary or testis was observed through the histological samples. Based on these findings, it can be concluded that at 9 month-old, Kerai Lampam is still at immature stage, therefore cannot be used for reproduction.